Preliminary insights into late prehistoric fish procurement strategies in the desert interior of southeastern Arabia: The results of LA-ICP-MS analysis of a fish otolith assemblage from Saruq al-Hadid, UAE. (August 2019) - Roberts, James; Weeks, Lloyd; Fillios, Melanie; Cable, Charlotte; al-Ali, Yaaqoub Youssef; Boraik, Mansour; Zein, Hassan
Abstract: Fishing is known to have been an integral component of life in prehistoric coastal communities in southeastern Arabia and the recovery of fish bones from sites away from the coast indicates that fish were also an important resource at inland sites in this area. Recent excavations undertaken at the late prehistoric (c.2000–c.800 BCE) site of Saruq al-Hadid, UAE, a desert site located c.40 km away from Emirate of Dubai's coastline, have recovered a large assemblage of fish remains including a substantial number of sagittal otoliths from a variety of marine species. In this paper, we present the results of Laser Ablation ICP-MS analysis of the chemical composition of 143 sagittal otoliths recovered from Saruq al-Hadid and use the data to make preliminary inferences regarding the provenance, season of capture and method of preservation of these fish. We tentatively suggest that the otolith chemistries observed in this study indicate that fish from both the Persian Gulf and Omani coast are present at Saruq al-Hadid. Additionally, we are also able to rule out salting as a preservation method for the fish represented by these otoliths. However, we also highlight the extensive array of variables that may influence these data and acknowledge that the nature of the dataset prevents any firm conclusions being drawn regarding these topics at this stage in the study. Despite the limitations of this preliminary study, we argue that the otoliths from Saruq al-Hadid have significant research potential and conclude by outlining methods that might be employed to take this study further in the future. Highlights: The movement of marine resources around the landscape of prehistoric southeast Arabia is a well evidenced phenomenon. Furthering the understanding of the dynamics of this movement is an important research goal. The analysis of fish otolith chemistry from prehistoric sites is potentially a key method with which to accomplish this. A large assemblage of fish sagittal otoliths have been recovered from Saruq al-Hadid, dating the Bronze & Iron Ages. The chemistry of these otoliths has been analysed using LA ICP-MS. The results of this analysis provide tentative insights into the dynamics of regional fish movement during this period.